Form and Work in Music - Ildar Khannanov (Musica Theorica)
The two major categories, musical form and musical work have been in the center of attention for generations of theorists. Their relationship has been rather dramatic, as seen in the cases that took place in German, Russian and North American traditions. It is not, however, for the minute interest or for the satisfaction of the appetite for sensation that a historian of music theory may be interested in contemplation on this issue. The comparison of form to work does not generate a binary opposition. Rather, it is a natural phenomenon: things happen this way and the two schools of theorists emerged and kept maintaining strong beliefs in either form or work. With the necessary references to philosophy, to the questions of ontology and epistemology of these fundamental categories, the author presents the history of debates of formalists and integralists in both dimensions of research and pedagogy. In the end of the article, the author attempts to summarize this antinomy and to find a possible common ground for its evaluation within a single frame of thought.